Proceedings of the Ocean Drilling Program 1993
DOI: 10.2973/odp.proc.sr.132.301.1993
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic Ash and Pumice at Shatsky Rise: Sources, Mechanisms of Transport, and Bearing on Atmospheric Circulation

Abstract: Air-fall volcanic ash and pumice were recovered from 22 intervals in upper Miocene-Pleistocene nannofossil oozes cored in Hole 8IOC on Shatsky Rise, northwest Pacific. Shatsky Rise is near the eastern limit of ash falls produced by explosive volcanism in arc systems in northern Japan and the Kuriles, more than 1600 km away. Electron probe analyses establish that the ash beds and pumice pebbles are andesitic to rhyolitic in composition, and belong to both tholeiitic and high-alumina lineages similar to tephra f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Compositional studies on tephra from ODP drill sites on Shatsky Rise (Arculus et al 1995;Natland 1993), 1600 km downwind from the Kuriles arc and west of Central America (Cadet et al 1982a, b), confirmed this link. However, the origin of volcanic glasses in DSDP leg 54 and ODP leg 138 sites approximately 2000 km west of Central America remains questionable.…”
Section: Constraints From Spatial Distributionsupporting
confidence: 53%
“…Compositional studies on tephra from ODP drill sites on Shatsky Rise (Arculus et al 1995;Natland 1993), 1600 km downwind from the Kuriles arc and west of Central America (Cadet et al 1982a, b), confirmed this link. However, the origin of volcanic glasses in DSDP leg 54 and ODP leg 138 sites approximately 2000 km west of Central America remains questionable.…”
Section: Constraints From Spatial Distributionsupporting
confidence: 53%
“…Typical respective clastic particle sizes for the central North Pacific are from (1) Rea [], (2) Natland [], and (3) Yamazaki and Ioka []. From the magnetic sources (1)–(4) above, we deduce that only (1) contributes to HIRM, (2) and, less, (1) contribute to IRM 20mT , and (3) plus submicrometer magnetic inclusions of all other fractions contribute to ARM.…”
Section: Proxy Records Of Core So202‐39‐3mentioning
confidence: 98%
“…Intercalated fine volcanic ash and pumice layers (mostly 1–2 cm, some 10 cm) are frequent in sediments from the Shatsky Rise area and have been backtracked to recently active volcanoes on Hokkaido and the Kuril Islands [ Natland , ]. According to Natland's estimates, the number of observable tephra layers per Myrs should decline from ~30 in the west to ~5 in the east of our core transect.…”
Section: Hydrography and Sedimentology Of The Northwest Pacificmentioning
confidence: 99%
“…A study of volcanic ash layers from ODP site 810C on the Shatsky Rise just south of station 40 (Fig. 1) indicates contributions from the Kurile Islands, Kamchatka and Hokkaido (Natland, 1993). Volcanic material from Hokkaido probably does not contribute to ODP site 881 off the Kurile Islands (Fig.…”
Section: Local Uncertainties In the Lithogenic Component Deconvolutionmentioning
confidence: 99%
“…These regions are characterized by an excess pool of macronutrients delivered to the euphotic zone by mixing that is incompletely consumed during the annual biogeochemical cycle (Falkowski et al, 1998). The incomplete consumption has been explained by a lack of dissolved iron for which eolian dust is suggested to be the primary source in the SNP (e.g., Bishop et al, 2002;Duce and Tindale, 1991;Martin and Fitzwater, 1988;Martin et al, 1989; (Natland, 1993) and 881-882 (Cao et al, 1995a). ODP site 887 (Cao et al, 1995b) and MD02-2489 (Gebhardt et al, 2008) are located near stations 26-28, RAMA 44PC (Keigwin et al, 1992) is located near station 5 and the site of core RC10-196 (Kohfeld and Chase, 2011) is located near station 13.…”
Section: Introductionmentioning
confidence: 99%